Fabrication and characterization of cane fiber reinforced unsaturated polyester resin composites (Bangladesh Journal of Scientific and Industrial Research, 2019)
Cane fiber of the generas Acoruscalamus, Daemonorops Draco, Daemonoropsmollis climbing palms of tropical Asia, belonging to the family palmae (palm family) and unsaturated polyester resin were used for the preparation of composites. Cane fiber was modified with 5%, 10%, 15% NaOH solution. Various physical and mechanical properties of the composite for different orientations of fiber were measured. The physical properties i.e. water absorption of treated fiber reinforced composites is lower. But the moisture content of cane fiber decreases with higher concentration of alkali solution used for treatment. The ultimate tensile strength (UTS) is higher for treated fiber reinforced composites than the raw fiber reinforced composites for any types of orientations of fibers and the tensile strain of treated fiber reinforced composites is lower than the raw fiber reinforced composites. The UTS value for treated cane fiber composites increases with increasing weight percentage of fiber than the raw fiber reinforced composite.Bangladesh J. Sci. Ind. Res.54(3), 247-256, 2019